KEPEMIMPINAN BUDAYA KERJA ISLAMI DALAM MENINGKATKAN KINERJA PENDIDIKAN AGAMA ISLAM - Firdausi, Rizqi Ahla; Miftahudin, Ujang; Abdul Kudus, Endang Dudus (Expectation: Journal of Islamic Education Management, 2025)
Education plays a crucial role in shaping human character, but the challenges of the 21st century underscore the importance of effective leadership. The concept of Islamic work culture leadership emerges as a promising alternative. This article uses a qualitative approach to explore its impact on the performance of Islamic religious education. The results indicate that leadership based on Islamic work culture creates a harmonious work environment, increases motivation, and strengthens individual self-esteem in Islamic religious educational institutions. Performance evaluation and consistency in implementing Islamic values ​​are key to success. Despite the challenges, implementing this approach has the potential to significantly contribute to the quality of Islamic religious education.